The wicked and the dead : the hair-raising tale of Hack Long and his outlaw gang - Johnstone, William W.; Johnstone, J. A. (Pinnacle Books, Kensington Publishing Corporation, 2024)
When Hack Long and his outlaws break out of jail and split up to escape, they each find themselves scrabbling along a desolated landscape, heading for Texas to reclaim their stolen gold, while being hunted by lawmen, Comanches and violent gang who also want their ill-gotten gains.